The Balaghah Learning Model at Islamic Boarding Schools Musthafawiyah Purba Baru - Rita Gamasari; Fauzul Fil Amri; Yasmadi Yasmadi (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This research explores the balaghah learning model at the Musthafawiyah Purba Baru Islamic Boarding School with the main aim of identifying uniqueness in its learning approach. Qualitative descriptive methods are used to describe the results of field observations systematically and in detail. From this research, five crucial aspects were revealed. First, the use of the book Jauharul Maknun as balaghah learning material is supported by the in-depth Arabic language skills of senior teachers. Second, the qawaid wa tarjamah method applied not only strengthens students' obedience to teachers, but also faces challenges such as registration which takes a long time, hinders the achievement of material targets, and does not stimulate students' active thinking. Third, there needs to be stronger integration between teacher-centered and student-centered approaches to build balanced collaboration between students and teachers, as well as increase student involvement in the learning process. Fourth, enriching the qiyasyah method with local examples can increase students' insight and motivation in studying balaghah. Fifth, learning evaluation does not only utilize summative tests, but also requires formative tests to improve learning outcomes on an ongoing basis.